2016
DOI: 10.1186/s40463-016-0171-1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of laryngopharyngeal reflux on subjective and objective voice assessments: A prospective study

Abstract: BackgroundLaryngopharyngeal reflux is a prevalent, not well-understood disease affecting a high proportion of patients who seek laryngology consultation. The objective of this prospective case series is to explore the subjective and objective voice modifications in Laryngopharyngeal reflux (LPR), especially the usefulness of acoustic parameters as treatment outcomes, and to better understand the pathophysiological mechanisms underlying the development of voice disorder.MethodsForty-one patients with a reflux f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0
4

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 43 publications
3
43
0
4
Order By: Relevance
“…Because LPR‐related symptoms are associated with QoL impairments, we wanted to include in the RSS a QoL assessment related to the underlying symptoms. Our analysis confirmed the impact of reflux on patient QoL and identified some symptoms that were associated with significant QoL impairment, such as throat pain, heartburn, throat clearing, globus sensation, and excess throat mucus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because LPR‐related symptoms are associated with QoL impairments, we wanted to include in the RSS a QoL assessment related to the underlying symptoms. Our analysis confirmed the impact of reflux on patient QoL and identified some symptoms that were associated with significant QoL impairment, such as throat pain, heartburn, throat clearing, globus sensation, and excess throat mucus.…”
Section: Discussionmentioning
confidence: 99%
“…Six impedance segments were placed along the esophagus zones (Z1 to Z6) and centered at 19,17,11,9,7, and 5 cm above the lower esophageal sphincter (LES). The last two impedance segments were placed 1 and 2 cm above the upper esophageal sphincter in the hypopharyngeal cavity.…”
Section: Impedance-ph Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…To improve the management of LPR patients, Belafsky et al developed RSI and RFS, two reliable scales that are widely used for LPR diagnosis and follow‐up throughout the world . Many studies found that total scores of RSI and RFS improved from baseline to 3 or 6 months post‐treatment, but a few trials were really interested in the evolution of individual symptoms and signs along the empirical therapeutic course. Moreover, we often see in our clinical practice that many patients need over 3 months of treatment to completely be cured.…”
Section: Discussionmentioning
confidence: 99%
“…Seven studies were excluded due to overlapping patient populations. 78,[87][88][89][90][91][92] Two placebo RCTs included in previous meta-analysis 93 were excluded because focusing on patients with chronic cough attributed a posteriori to LPR. 94,95 The degree of agreement between investigators was high because only three articles have been discussed about the inclusion.…”
Section: Resultsmentioning
confidence: 99%